Bidirectional Sensor-Based Measurement of PV Output with MPPT Control: An Experimental Pre-Study before PLC Monitoring Integration - Prasetyani, Lin; Abdillah Aziz Mumtasir; M. Akbar Faturahman; Bella Berliana (Universitas Muhammadiyah Sidoarjo, 2025)
This paper presents a preliminary experimental study on the use of an analog bidirectional current sensorfor photovoltaic (PV) systems operated under Maximum Power Point Tracking (MPPT) control. The ultimate goalof this research is to develop a comprehensive monitoring system for energy harvesting from PV systems using aPLC-based platform. As an initial step, this study investigates the behavior of a bidirectional sensor in detectingcharging and discharging processes in an off-grid PV configuration. The sensor is evaluated through experimentalmeasurements of current and voltage outputs, where the bidirectional characteristic provides an indication of thedirection of energy flow—charging when energy is stored in the battery and discharging when energy is supplied tothe load. Data acquisition and visualization are performed using LabVIEW, which allows real-time monitoring andvalidation of sensor performance at specific time intervals. The experimental results provide insights into theaccuracy and reliability of the analog bidirectional sensor under varying operating conditions. The novelty of thisstudy lies in its focus on sensor behavior analysis as a foundation for future PLC-based monitoring systemdevelopment. By validating sensor performance through this pre-study, the research ensures that reliable data canbe obtained for subsequent integration into a real-time monitoring and control system for PV energy harvestingapplications